Bta-miR-365-3p-targeted FK506-binding protein 5 participates in the AMPK/mTOR signaling pathway in the regulation of preadipocyte differentiation in cattle - Mengdi Chen; Congcong Zhang; Zewen Wu; Siwei Guo; Wenfa Lv; Jixuan Song; Beibei Hao; Jinhui Bai; Xinxin Zhang; Hongyan Xu; Guangjun Xia (Animal Bioscience, 2024)
Objective MicroRNAs (miRNAs) are endogenous non-coding RNAs that can play a role in the post-transcriptional regulation of mammalian preadipocyte differentiation. However, the precise functional mechanism of its regulation of fat metabolism is not fully understood. Methods We identified bta-miR-365-3p, which specifically targets the 3′ untranslated region (3′UTR) of the FK506-binding protein 5 (FKBP5), and verified its mechanisms for regulating expression and involvement in adipogenesis. Results In this study, we found that the overexpression of bta-miR-365-3p significantly decreased the lipid accumulation and triglyceride content in the adipocytes. Compared to inhibiting bta-miR-36 5-3p group, overexpression of bta-miR-365-3p can inhibit the expression of adipocyte differentiation-related genes C/EBPα and PPARγ. The dual-luciferase reporter system further validated the targeting relationship between bta-miR-365-3p and FKBP5. FKBP5 mRNA and protein expression were detected by quantitative real-time polymerase chain reaction and Western blot. Overexpression of bta-miR-365-3p significantly down-regulated FKBP5 expression, while inhibition of bta-miR-365-3p showed the opposite, indicating that bta-miR-365-3p negatively regulates FKBP5. Adenosine 5′-monophosphate (AMP)-activated protein kinase/mammalian target of rapamycin (AMPK/mTOR) signaling pathway is closely related to the regulation of cell growth and is involved in the development of bovine adipocytes. In this study, overexpression of bta-miR-365-3p significantly inhibited mRNA and protein expression of AMPK, mTOR, and SREBP1 genes, while the inhibition of bta-miR-365-3p expression was contrary to these results. Overexpression of FKBP5 significantly upregulated AMPK, mTOR, and SREBP1 gene expression, while inhibition of FKBP5 expression was contrary to the above experimental results. Conclusion In conclusion, these results indicate that bta-miR-365-3p may be involved in the AMPK/mTOR signaling pathway in regulating Yanbian yellow cattle preadipocytes differentiation by targeting the FKBP5 gene.